Meningkatkan Kreatifitas Peserta Didik Pada Pembelajaran Pak Dan Bp Dengan Metode Pbl Kelas VIII SMP Negeri 1 Siempatnempu - Pasti Melina Nainggolan; Timotes Tote Jelahu; Modestus Haryono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education is one of the basic needs required by every human being and an obligation that must be obtained by every citizen. The development of human life from time to time is certain to be more complex, especially in the development of science and technology. This requires humans to always be able to compete in keeping up with developments and be able to survive by being able to solve all the problems they face. Therefore, a student's ability to think critically is an important and primary thing. Critical thinking skills will be very beneficial for students because they will understand a problem in detail, so it is expected that students will find it easier to solve the problem. For this reason, learning that emphasizes critical thinking skills must be implemented in schools, especially at the junior high school level, which is the middle level of education and is a stepping stone to a wider social interaction. The purpose of this study was to determine the effect of applying the Problem-Based Learning model in improving critical thinking attitudes in Catholic Religious Education and Ethics learning for seventh-grade students with the theme "I Have Abilities and Limitations" at SMP Negeri 1 Temanggung. The type of research used is quantitative. This method is called the traditional method because it has been used for quite some time so it has become a tradition as a method for research. Quantitative research is research in which the data is presented in the form of numbers and uses statistical analysis, usually aimed at showing the relationship between variables, testing theories, and finding generalizations that have predictive value. The researcher uses a quantitative method because it is necessary to measure data in research related to Fostering Critical Thinking Attitudes of Students Through the Problem-Based Learning Model in Catholic Religious Education and Ethics Subjects for Grade VII students at SMP Negeri 1 Temanggung. The type of research often used by a researcher in the field of education is experimental. This type of research is used to find out the influence of certain treatments on a variable under controlled conditions. This is applied to find out the effect if the problem-based learning (PBL) learning model treatment is given to the critical thinking abilities of seventh-grade students in Catholic Religious Education and Ethics.